Novel transition metal-free synthetic protocols toward the construction of 2,3-dihydrobenzofurans: a recent update - Mushtaq, Aqsa; Irfan, Muhammad; Haq, Atta ul; Mansha, Asim; Khan, Samreen Gul; Zahoor, Ameer Fawad; Parveen, Bushra; Irfan, Ali; Kotwica-Mojzych, Katarzyna; Glowacka, Mariola; Mojzych, Mariusz (Frontiers in Chemistry, 2024)
2,3-Dihydrobenzofurans are noteworthy scaffolds in organic and medicinal chemistry, constituting the structural framework of many of the varied medicinally active organic compounds. Moreover, a diverse variety of biologically potent natural products are also embodied with this heterocyclic nucleus. Reflecting on the wide biological substantiality of dihydrobenzofurans, several innovative and facile synthetic developments are constantly evolving to achieve these heterocycles. This review summarizes the transition metal free, efficient and novel synthetic pathways towards the construction of dihydrobenzofuran nucleus, established post 2020.